2010
DOI: 10.1007/s12648-010-0020-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cloud on atmospheric ozone formation over Kolkata (22°34′N, 88°24′E), India

Abstract: The paper presents the nature of variations of clouds and total ozone over Kolkata (22 o 34 / N, 88 o 24 / E), India. The low-level cloud over Kolkata has been noticed to occur for many days and nights, particularly in the months from June to September. The low level cloud occurrences were minimum in winter months. The effect of cloud occurrence on ozone concentration has been critically analyzed and explained. It has been observed that the concentration of ozone increased with the increase of cloud occurrence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 21 publications
(14 reference statements)
0
5
0
Order By: Relevance
“…Ozone concentration attained higher value at moderate cloud occurrences and lower value at both lower and higher cloud occurrences due to higher solar radiation and moderate concentration of ozone precursors at moderate cloud occurrences and comparatively lower solar radiation energy at both the lower and higher range of cloud occurrences. Again very low negative correlation coefficient value of cloud occurrences (−0.25) and high correlation coefficient value of surface solar radiation (0.73) signifies insignificant contribution of cloud occurrences and significant contribution of surface solar radiation on tropospheric ozone formation processes over Alipore, though cloud occurrences play a significant role in total ozone column density over Kolkata (Jana et al 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ozone concentration attained higher value at moderate cloud occurrences and lower value at both lower and higher cloud occurrences due to higher solar radiation and moderate concentration of ozone precursors at moderate cloud occurrences and comparatively lower solar radiation energy at both the lower and higher range of cloud occurrences. Again very low negative correlation coefficient value of cloud occurrences (−0.25) and high correlation coefficient value of surface solar radiation (0.73) signifies insignificant contribution of cloud occurrences and significant contribution of surface solar radiation on tropospheric ozone formation processes over Alipore, though cloud occurrences play a significant role in total ozone column density over Kolkata (Jana et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…It strengthened the circulation, leading to decrease in total tropical ozone. Jana et al (2010) reported the significant rise of total atmospheric ozone column density with increase in cloud occurrences not considering other meteorological parameters. In this paper, the nature of annual cycles of tropospheric ozone, cloud occurrences, NO 2 , rainfall, SO 2 , suspended particulate matter (SPM), CO, NMHC and surface solar radiation for the period October 2004 to June 2009 has been shown and explained over Alipore (22.52 • N, 88.33 • E), India.…”
Section: Study Of Cloud Chemistrymentioning
confidence: 99%
“…Total column ozone densities of different stations have been obtained from the website http://jwocky. gsfc.nasa.gov (Jana et al 2010a(Jana et al , 2010b. Monthly mean ozone densities have been calculated from daily average value of ozone in DU for the stations, namely, New Delhi and Halley Bay.…”
Section: Data and Analysismentioning
confidence: 99%
“…It is greatly influenced by predominant meteorological conditions (temperature, solar flux, wind speed and relative humidity). Several authors have studied the possible interaction of surface temperature and cloud cover on ozone concentration (Liu et al 2006 ; Voulgarakis et al 2009 ; Jana et al 2010 , 2011 ; Midya et al 2011 ; Ghosh et al 2015 ). O 3 concentration increases with an increase in solar flux and temperature (Gorai et al 2015 ).…”
Section: Introductionmentioning
confidence: 99%